Multiple access interference suppression for direct-sequence code-division multiple access (DS-CDMA) communication systems - Chen, Wanshi. (2008)
DS-CDMA is one of the promising multiple access techniques for the third generation mobile communication system due to its high capacity potential and other desirable merits, such as flexibility, anti-multipath fading, soft hand-off and universal frequency reuse. The performance of the conventional detector for DS-CDMA communication systems is mainly limited by the multiple access interference (MAI) and the so-called near-far problem. Multiuser detectors, which have substantial performance gain over the conventional detector and, most importantly, achieve the near-far resistance capability, have attracted attention from researchers over the past decade.